Salmonella septic arthritis in a patient with acute idiopathic thrombocytopenic purpura treated with steroid - Kanra, Güler; Seçmeer, Gülten; Toyran, Müge; Cengiz, A. Bülent; Değertekin, Yasemin; Kara, Ateş (The Turkish Journal of Pediatrics, 2000)
Salmonella has three clinical presentations: self-limiting gastroenteritis, a systemic syndrome (enteric or typhoid fever), and bacteremia with focal infection. Hematogenous infections can cause focal lesions, but unusual manifestations occur more often when predisposing factors such as T cell defect, hemolytic disorders (sickle cell disease, malaria) or trauma are present. Salmonella tend to invade bones and joints. There is no mention of acute idiopathic (immune) thrombocytopenic purpura as a predisposing factor for salmonella septic arthritis; however there are reports about the importance of platelets for the immune response. Here we present a case of Salmonella enteritidis septic arthritis following acute idiopathic (immune) thrombocytopenic purpura in a 15-year-old female patient who has been on steroid therapy for the last two weeks.
Keywords: idiopathic thrombocytopenic purpura; septic arthritis; Salmonella enteritidis; steroid therapy